CIENTIFICOS GRIEGOS - Vera, Francisco (1970)
CONTENIDO: V.1 PITAGORAS, HIPOCRATES, DEMOCRITO, PLATON, ARISTOTELES, TEOFRASTO, EUDEMO DE RODAS, EUCLIDES, ARISTARCO.--V.2 ARQUIMIDES, APOLONIO DE PERGAMO, ERATOSTENES, NICANDRO, HIPARCO, TEODOSIO DE TRIPOLI, HERON DE ALEJANDRIA, DIOSCORIDES, PTOLOMEO, GALENO, NICOMACO DE GERASA, PAPPO, DIOFANTO DE ALEJANDRIA, PROCLO DE LICIA